Hubungan antara Konsep Diri dengan Kepatuhan Berobat pada Lansia Hipertensi di Puskesmas Wanadadi 2 Banjarnegara - Yuana Kartika; Wastu Adi Mulyono; Akhyarul Anam (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Background : Being old is a natural ageing process. Physical changes occur and may disturb elderly self-concept. Disruption of the self-concept can influence other factors, such as self-care ability that may affect medical check-up compliance. This study aims to determine the relationship between self-concept and medical check-up compliance among elderly with hypertension. Methods : A Quantitative research invited 56 elderlies with hypertension at Puskesmas Wanadadi 2 as samples. A consecutive sampling technique was applied. A set of questionnaires used during data collection. Hypothesis was tested on the Fisher Exact test. Results : The results showed that the respondents had an age range of 60-82 years, which mostly suffered by female respondents. Most of the respondents attend school up to elementary school and work as entrepreneurs and housewives. The majority of respondents had a history of hypertension for ≤ 5 years. The results from the bivariate analysis shows a significance value is 0,000 which means there is a relationship between self-concept and medical check-up compliance in the elderly with hypertension. Conclusion : There is a relationship between self-concept and medical check-up compliance among elderlies with hypertension at Puskesmas Wanadadi 2. Keywords : Compliance, elderly, education, hypertension, self-concept.